MEJA KERJA DENGAN ALAT PEMBUAT LUBANG PEN UNTUK MENINGKATKAN KUALITAS DAN KEqEPATAN ABSTRACT PEMBUATAN PINTU KAYU - -, Didik Nurhadiyanto; S, Suprapto Rachmad (Universitas Negeri Yogyakarta, 2004)
Inmakingwoodcraftingspeciallymakingof door andshutter leaf oftentimesobtaineda handicappeddoor productat shares penholein the formof barst / break,thedifficultymakethedoorleafifmarket requestquitea lot,and narrowtightworkplaceSothat neededa workbenchwhichmuliti functionso that allworkabledoormakingworkthedesk.Consideringproblemsfacedby this wood industryhencetheindustryrequiretobe assistedbygivena applianceofdoor maker inthelbnnof aworkbenchof multifunction providedby theapplianceofholepenmaker.Withtheworkbenchall workercan finishthe workof doormaking startfrom cuttingr.rfworkpiece.making of holepencomeup with thesetting.The aim ofthisprogramis toperformandmaketheworkbenchby meansof holepento increasequalityand timeefficiency,so thatsmallindustrycan do themoreorder.Inexecutingthis prograrnwe takethe followingstages :(l)planningworkbenchtoproducethe leafofdoor or window,matchingwithsociety condition.Sothat thisapplianceeasyto acceptedby society hencethis applianceown thefollowingspecification:Easy tooperate it,economizethe place,workof makingof'door leafbecomeeasier,(2)testingworkbenchto makedoorinwoodindustryindustry